Selective inactivation of Gram-negative bacteria by carbon dots derived from natural biomass: Artemisia argyi leaves. Issue 13 (6th March 2020) - Wang, Huibo; Zhang, Mengling; Ma, Yurong; Wang, Bo; Shao, Mingwang; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : Carbon dots derived from Artemisia argyi leaves exhibit specific antibacterial activities on Gram-negative bacteria. Abstract : Infections caused by Gram-negative bacteria have been an increasing problem worldwide. Meanwhile, the overuse of traditional antibiotics has caused an emergence of drug resistance. The development of new antibacterial agents, which can cope with the threat from drug-resistant bacteria, is urgently needed. Herein, carbon dots (ACDs) derived from Artemisia argyi leaves were obtained via a smoking simulation method and exhibited selective antibacterial ability of targeting Gram-negative bacteria. The bactericidal efficiency of ACDs (150 μg mL −1 ) for Gram-negative bacteria ( Escherichia coli, Pseudomonas aeruginosa, and Proteusbacillus vulgaris) can reach 100%, while for Gram-positive bacteria ( Staphylococcus aureus and Bacillus subtilis ), ACDs have no significant antibacterial function, indicating that the particles can selectively target specific bacteria. The antibacterial mechanism for ACDs confirmed that ACDs could only damage the cell walls of Gram-negative bacteria but not that of Gram-positive bacteria. Moreover, ACDs can inhibit the activity of cell wall-related enzymes in Gram-negative bacteria by changing the enzymatic secondary structure. This work is of great significance for the development of new antibacterial nanomaterials derived from natural biomass as well as the treatment of infections caused by Gram-negative bacteria.